Legal Implications of Equalization Administrative Position Become The Functional Position In The Government Of Riau Islands - Hani Marta Theodora; Pery Rehendra Sucipta; Irman Irman (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2023)
In the end of 2021, The Government Riau Islands Province appointed 415 affected officials, of which 17 Adminstrative Officers Head Of The Finance Sub Division transffered to Functional Officers for Central and Regional Finansial Analysis (AKPD). Problems in this research are, how is the implementation of the regulation of The Ministry Of Adminitrative and Bureaucratic Reform Number 17 of 2021 concerning the equalization of administrative Positions into functional Positions in The Government Of Riau Islands and the legal implications for officials affected after the position of The Head of The Finance Sub Division transferred to the Functional Position Central and Regional Finance Analysis. The purpose of the research are investigates the implementation of the regulation and the legal impact for the officers affected. In accordance with the issues to be discussed in this study and in order to provide usefull results, this research method used normative (normative legal research method). The hypothesis of the research is the implementation raised many legal problems such as violated the principal of lex superior derogat legi inferior and making the affected officials have no legal certainty in carrying out the duties of their position.